STRATEGIES AND REALITIES OF INTEGRATION OF DOMESTIC ENTERPRISES INTO THE INTERNATIONAL BUSINESS ENVIRONMENT - KARACHYNA, NATALIA; SEMTSOV, VOLODYMYR; SMETANIUK, OLENA; BALZAN, MARINA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article defines the essence, role and significance of economic strategies in the context of integrating domestic market agents into the international business environment. The main aspects of defining the concept of "strategy" are studied, and on this basis, the effects and phenomena that are implemented in the general economic theory are described and formalized. Based on the identification of the category of "strategy" in the context of various scientific approaches, the correctness of the author’s research methodology is proven. The potential and main problems faced in the process of working up economic strategies for the development of integrated enterprises are identified, as well as the main threats posed to the evolution of market agents as a result of incorrect choice of strategic management tools are outlined. The categories of "strategy - economic behaviour" have been formalized following the author’s concept, which outlines key similarities and differences. The main features of economic strategies are formed and generalized. It is emphasized that the international business environment is actively used by domestic integrated enterprises as a channel for removing financial resources outside the country. Particular attention is paid to the negative consequences of tax minimization, including the cases of reinvoicing (change in the price of goods) under the conditions of using non-resident companies. Emphasis is given to the main ways of stopping dysfunctional economic processes. It is established that from the point of view of the destructiveness of economic processes, the corresponding dysfunctions of strategy formation are a direct consequence of unjustified liberalization of the legislation. It is defined that the institutional environment itself is one of the key factors of ensuring the effectiveness and efficiency of undergoing a socio-economic change in the context of implementing strategies for the development of integrated enterprises. It is pointed out that the dysfunctions of economic reform, including the destructive models of economic behaviour of enterprises, have become, in fact, a natural consequence of thoughtless institutional changes.